Moving and unsinkable graphene sheets immobilized enzyme for microfluidic biocatalysis - An Gong; Chang-Tong Zhu; Yan Xu; Fang-Qin Wang; D’assise Kinfack Tsabing; Fu-An Wu; Jun Wang (Scientific Reports, 2017)
Abstract Enzymatic catalysis in microreactors has attracted growing scientific interest because of high specific surface enabling heat and mass transfer and easier control of reaction parameters in microreactors. However, two major challenges that limit their application are fast inactivation and the inability to the biocatalysts in microchannel reactors. A fluid and unsinkable immobilized enzyme were firstly applied in a microchannel reactor for biocatalysis in this study. Functionalized forms of graphene-immobilized naringinase flowing in microchannels have yielded excellent results for isoquercitrin production. A maximum yield of 92.24 ± 3.26% was obtained after 20 min in a microchannel reactor. Ten cycles of enzymatic hydrolysis reaction were successively completed and an enzyme activity above 85.51 ± 2.76% was maintained. The kinetic parameter V m/K m increased to 1.9-fold and reaction time was decreased to 1/3 compared with that in a batch reactor. These results indicated that the moving and unsinkable graphene sheets immobilized enzyme with a high persistent specificity and a mild catalytic characteristic enabled the repetitive use of enzyme and significant cost saving for the application of enzyme catalysis. Thus, the developed method has provided an efficient and simple approach for the productive and repeatable microfluidic biocatalysis.